2018
DOI: 10.1002/joc.5515
|View full text |Cite
|
Sign up to set email alerts
|

Drought characteristics over China during 1980–2015

Abstract: The self‐calibrating Palmer drought severity index (scPDSI) was computed based on the four atmospheric reanalysis data sets combined with observational data over China during 1980–2015. The discrepancies of scPDSI among the four reanalysis data sets show the necessity of integrating multiple data sets. Drought characteristics, such as drought area, severity, duration, and frequency were examined based on multi‐data set mean scPDSI. The results reveal that significant drying trends are found in Qinghai‐Tibet Pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
52
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 54 publications
5
52
0
Order By: Relevance
“…The features of droughts have changed significantly due to climate change impact on rainfall parameters such as frequency, intensity and distribution of rainfall (Azam et al, 2018;Shao et al, 2018). Blenkinsop and Fowler (2007) reported a decrease in duration but an increase in the intensity of droughts in Britain.…”
Section: Introductionmentioning
confidence: 99%
“…The features of droughts have changed significantly due to climate change impact on rainfall parameters such as frequency, intensity and distribution of rainfall (Azam et al, 2018;Shao et al, 2018). Blenkinsop and Fowler (2007) reported a decrease in duration but an increase in the intensity of droughts in Britain.…”
Section: Introductionmentioning
confidence: 99%
“…They can be grouped into four types including meteorological drought (deficiencies of precipitation), agricultural drought (lack of soil moisture affecting crop development or plant growth), hydrological drought (shortfall on water, such as decreased streamflow or low levels in lakes or reservoirs) and socioeconomic drought (impacts of drought on the supply and demand of certain economic goods) [3]. Due to their high frequency and tremendous damage, evaluations of drought variabilities have attracted increasing attentions in recent studies [1,2,[5][6][7][8]. A multitude of studies have been devoted to the historical assessment of droughts based on different indices and showed the increased risk of droughts under global warming [5,9].…”
Section: Introductionmentioning
confidence: 99%
“…Andreadis et al [37] created a severity-area-duration (SAD) analysis method, which regards drought as an individual event. This method combines severity, area (extent), and duration of drought events to effectively analyze changes in the drought characteristics of different regions (e.g., Xiao et al [38]; Shao et al [39]). For example, Sheffield et al [40] used cluster analysis and the SAD method to analyze global and continental drought characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [43] used the SAD method to analyze the spatial and temporal evolution of drought events between 2000 and 2008 in the Colorado River basin, USA. Shao et al [39] used SC-PDSI index and SAD method to analyze the drought characteristics of recent decades , and found that both methods can capture well the historical drought events of China.…”
Section: Introductionmentioning
confidence: 99%